(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Abstract Local governance plays a pivotal role in shaping the health and wellbeing of communities through the design and implementation of effective public policies. This paper examines the mechanisms by which local authorities influence community health, exploring the intersection between governance structures, participatory decision-making, and policy outcomes. Drawing upon theoretical frameworks and real-world examples, it highlights how localized policy interventionsranging from preventive healthcare programs to social welfare initiativescan significantly improve health outcomes. Furthermore, it discusses the challenges that local governments face, such as limited resources and political constraints, and offers recommendations for fostering inclusive, evidence-based policymaking.